2023
DOI: 10.1002/adma.202308344
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Vesicle Assemblies with DNA Nanorulers for Resolving Heterogeneity of Vesicles in Live Cells

Yueyue Zhang,
Jiangbo Liu,
Xiuhai Mao
et al.

Abstract: Nanoscale vesicles such as synaptic vesicles play pivotal role in efficient inter‐neuronal communications in vivo. However, the co‐existence of single vesicle and vesicle clusters in living cells increases the heterogeneity of vesicle populations, which largely complicates the quantitative analysis of the vesicles. Hence, the high spatiotemporal monitoring of vesicle assemblies is currently incompletely resolved. Here, we used synthetic vesicles and DNA nanorulers to reconstruct in vitro the vesicle assemblies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Under KCl stimulation, the current first rises sharply, producing spike I within 30 s and then falls to baseline as dopamine is rapidly metabolized, and the stimulus-generated dopamine is 6.5–7.6 μM [ I (nA) = 0.16 C DA (μM) + 0.06, r = 0.9998]. Interestingly, reproducible shoulder spike II (1.0–1.2 μM) is generated during the current drop, which behaves similarly to the kinetic process of the neurotransmitter release from vesicles via exocytosis. Similarly, Zhang et al recently showed that such double spikes occurred when neighboring vesicles aggregate to form a dimer and that the distance between the vesicles correlated with the separation of the double spikes. Furthermore, they also recorded complex events in high K + -stimulated PC12 cells, such as single spikes, double spikes, and even multispikes.…”
Section: Resultsmentioning
confidence: 95%
“…Under KCl stimulation, the current first rises sharply, producing spike I within 30 s and then falls to baseline as dopamine is rapidly metabolized, and the stimulus-generated dopamine is 6.5–7.6 μM [ I (nA) = 0.16 C DA (μM) + 0.06, r = 0.9998]. Interestingly, reproducible shoulder spike II (1.0–1.2 μM) is generated during the current drop, which behaves similarly to the kinetic process of the neurotransmitter release from vesicles via exocytosis. Similarly, Zhang et al recently showed that such double spikes occurred when neighboring vesicles aggregate to form a dimer and that the distance between the vesicles correlated with the separation of the double spikes. Furthermore, they also recorded complex events in high K + -stimulated PC12 cells, such as single spikes, double spikes, and even multispikes.…”
Section: Resultsmentioning
confidence: 95%